Pattern analysis of sorghum genotype x environment interaction for leaf, panicle, and grain anthracnose in Mali - Hess, D.E.; Bandyopadhyay, Ranajit; Sissoko, I. (2002)
Resistance to anthracnose, caused by Colletotrichum graminicola, in sorghum was identified through field screening at two locations (Samanko and Longorola) in Mali. The occurrence and progress of anthracnose were monitored on 19 sorghum lines plus resistant and susceptible checks in the 1996 to 1998 rainy seasons. Foliar anthracnose severity was assessed at regular intervals throughout the season. Area under the disease progress curve (AUDPC) was calculated for each genotype. Anthracnose severity was also evaluated on the peduncle, rachis and glumes, panicle, and grain. For the characters under study, the site x year and site x year x line nteractions accounted for the genotype x environment interactions. Pattern analysis was applied to the environment-standardized matrix of genotype x environment means to analyze these interactions and elucidate genotypic adaptation. None of the lines was completely (hypersensitive) resistant to the disease, but 12 showed high levels of stable resistance to both foliar and panicle anthracnose. Only one was moderately susceptible to both forms of the disease. In addition to identifying varieties that can be grown in zones to which they are adapted, additional genotypes were identified that can serve as sources of resistance in regional breeding programs.